ANALISIS PENGENDALIAN KUALITAS PRODUK GARMEN DENGAN METODE SIX SIGMA PADA BAGIAN SEWING PT. RODEO PRIMA JAYA - Sarbullah Sarbullah; Sutrisno Sutrisno (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract The purpose of this research is to find out; 1) the production process in the sewing section of PT. Rodeo Prima Jaya; 2) the factors that cause defective products in the production process based on the six sigma stages, namely define, measure, analyze in the sewing section of PT. Rodeo Prima Jaya; 3) solutions that can be taken to reduce the number of defective products based on the six sigma stages, namely improvement and control in the sewing section of PT. Rodeo Prima Jaya; 4) the design of a garment product quality control system using the six sigma method in the sewing section of PT. Rodeo Prima Jaya. Sampling in this study used a sampling study approach. Sampling study approach is a research in which data is collected from some elements of the population. The samples used in this study were defective and recorded by the Quality Control section for 3 months, including: 1) June as many as 4867 defective products; 2) July as many as 5600 defective products, and 3) August as many as 5087 defective products.The results show that hypothesis 1 (H1) which states the level of product damage that occurs in the production process at PT. Rodeo Prima Jaya is still within the limits of the average sigma value. The dominant factors that cause defective products are machine factors, namely improper machine settings, inaccurate human factors and raw material factors, namely the presence of fabrics and threads that are not up to standard. Thus hypothesis 2 (H2) that the dominant factor that causes defective products at PT. Rodeo Prima Jaya is a factor of machines, people and raw materials. The improvement phase is related to the determination and implementation of solutions based on the results of the analysis that has been carried out in the previous stage, the solutions used to overcome the problem of defective products in the Sewing Section are applied to all the factors that cause the defective product. Thus hypothesis 3 (H3) that the solution used to overcome the problem of defective products in the sewing section is applied to all the factors that cause defective products. The sample is outside the control limits, the management must re-examine the fix solution that has been determined. Deviations occur because the solutions applied are not appropriate, both in terms of humans, methods, machines, raw materials and the environment. Thus hypothesis 4 (H4) that the level of product damage that occurs in the production process in the Sewing Section is still within the control limits.